Natural gas hydrates in flow assurance - Sloan, E. Dendy, 1944- (Gulf Professional Pub./Elsevier, 2011)
With millions of kilometres of onshore and offshore oil and gas pipelines in service around the world, pipelines are the life's blood of the world. Notorious for disrupting natural gas production or transmission, the formation of natural gas hydrates can cost a company hundreds of millions and lead to catastrophic equipment breakdowns and safety and health hazards. Written by an international group of experts, Natural gas Hydrates in Flow Assurance provide an expert overview of the practice and theory in natural gas hydrates, with applications primarily in flow assurance. Compact and easy to use, the book provides readers with a wealth of materials which include the key lessons learned in the industry over the last 20 years. Packed with field case studies, the book is designed to provide hands-on training and practice in calculating hydrate phase equilibria and plug dissociation. In addition readers receive executable programs to calculate hydrate thermodynamics. Case studies of hydrates in flow assurance The key concepts underlying the practical applications An overview of the state of the art flow assurance industrial developments.
Keywords: Petroleum pipelines -- Fluid dynamics.; Natural gas -- Hydrates.; Offshore oil well drilling -- Accidents -- Prevention.; Gas flow.; Natural gas in submerged lands.; elektronické knihy; electronic books